Thermal conduction across a boron nitride and SiO2 interface. (9th February 2017) - Li, Xinxia; Yan, Yaping; Dong, Lan; Guo, Jie; Aiyiti, Adili; Xu, Xiangfan; Li, Baowen
Abstract: The need for efficient heat removal and superior thermal conduction in nano/micro devices has triggered tremendous studies in low-dimensional materials with high thermal conductivity. Hexagonal boron nitride ( h -BN) is believed to be one of the candidates for thermal management and heat dissipation due to its novel physical properties, i.e. as a thermal conductor and electrical insulator. Here we report the interfacial thermal resistance between few-layer h -BN and its SiO2 substrate using the differential 3 ω method. The measured interfacial thermal resistance is around 1.6 × 10 −8 m 2 K W −1 for monolayer h -BN and 3.4 × 10 −8 m 2 K W −1 for 12.8 nm-thick h -BN in metal/ h -BN/SiO2 interfaces. Our results suggest that the voids and gaps between the substrate and thick h -BN flakes limit the interfacial thermal conduction. This work provides a deeper understanding of utilizing h -BN flakes as a lateral heat spreader in electronic and optoelectronic nano/micro devices with further miniaturization and integration.